Intellectual Property Rights and Science and Technology Innovation in China: Evidence and Theory - Jian Wang; Rui Chen (Data Science Journal, 2007)
This paper adopts the Panel Data Model based on the combination of time sequence and data of cross sections and does research on data of seventeen institutes in the Chinese Academy of Sciences. It makes empirical analysis of the Intellectual Property Rights (IPR) authorization and the relationship between R&D input and R&D scientific and technological output. Research results show that the role played by the Intellectual Property Rights Authorization in scientific and technological growth is notable and positively correlated.